Durvalumab with or without tremelimumab for patients with recurrent or metastatic squamous cell carcinoma of the head and neck: a systematic review and meta-analysis - Han, Xiao; Zhang, Haidong; Sun, Kai; Li, Jing; Wu, Wanjuan; Liu, Kai; Yu, Zhenkun (Frontiers in Immunology, 2024)
Objective: Head and neck squamous cell carcinoma (HNSCC) ranks as the sixth most prevalent cancer worldwide, significantly impacting patients' quality of life. Immune checkpoint inhibitors (ICI) have been employed in the treatment of recurrent/metastatic (R/M)-HNSCC patients. This meta-analysis aims to assess the efficacy and safety of durvalumab monotherapy compared to the combination of durvalumab and tremelimumab in R/M-HNSCC patients. Methods: Relevant studies were systematically searched in PubMed, Embase, and Cochrane Library databases. All articles comparing durvalumab monotherapy with the combination with durvalumab and tremelimumab in R/M-HNSCC treatment were included. Additionally, the references of identified studies were screened if necessary. Result: A total of 1298 patients from three studies comparing durvalumab with durvalumab and tremelimumab in treating R/M-HNSCC were include in this meta-analysis. Our findings revealed no significant difference in objective response rate (ORR) [odds ratio (OR): 1.15, 95% confidence interval (CI): 0.85 to 1.56, P = 0.36] and disease control rate (DCR) (OR=1.08, 95%CI: 0.86 to 1.37, P = 0.51). Similar outcomes were observed in overall survival (OS), progression-free survival (PFS), and duration of response (DoR). Regarding safety, there was no significant difference in the incidence of treatment-related adverse events (trAEs) between the two groups (OR=1.26, 95%CI: 0.81 to 1.94, P = 0.30). However, patients treated with the combination therapy exhibited a higher incidence of grade 3-4 trAEs (OR=1.93, 95%CI: 1.36 to 2.73, P = 0.0002) and a greater likelihood of discontinuing treatment due to trAEs (OR=2.07, 95%CI: 1.12 to 3.85, P = 0.02). There was no significant difference in the occurrence of severe trAEs leading to death (OR=1.36, 95%CI: 0.47 to 3.96, P = 0.57).This meta-analysis suggests that R/M-HNSCC patients receiving the combination of durvalumab and tremelimumab may achieve comparable outcomes in terms of ORR, DCR, OS, PFS, and DoR, without significant differences. However, the combination therapy is associated with a higher incidence of grade 3-4 trAEs and an increased likelihood of treatment discontinuation due to trAEs. These findings highlight the need for cautious consideration of the combination of durvalumab and tremelimumab in R/M-HNSCC patients, which should be further evaluated in highquality studies.